2021
DOI: 10.3390/economies9030128
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Information and Communication Technology (ICT) Use on Human Development—A Macroeconomic Approach

Abstract: Information and communication technology (ICT) is considered a significant factor in economic growth and development. Over the past two decades, scholars have studied the impact of ICT on economic growth, but there has been little research that has addressed the impact of ICT on human development, which is considered one of the fundamental factors of economic development. This could be especially important from the perspective of developing countries, which can develop faster through the implementation of ICT.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 37 publications
2
15
2
Order By: Relevance
“…Furthermore, Lee and Kim [ 16 ] identified that ICT increases the life expectancy at birth in the 16 Asian countries covering data of 2009–2014 from the fixed effect model. Similar results were also found by Afroz et al [ 39 ] for Malaysia, Aksentijevic [ 17 ] for 130 countries, Alzaid et al [ 40 ] for 156 countries, Kim and Kim [ 41 ] for 178 countries, Hashem [ 42 ] for developing countries. The ICT also reduces different types of mortality rates as found by Nyamawe and Seif [ 43 ] for Tanzania.…”
Section: Literature Reviewsupporting
confidence: 86%
See 2 more Smart Citations
“…Furthermore, Lee and Kim [ 16 ] identified that ICT increases the life expectancy at birth in the 16 Asian countries covering data of 2009–2014 from the fixed effect model. Similar results were also found by Afroz et al [ 39 ] for Malaysia, Aksentijevic [ 17 ] for 130 countries, Alzaid et al [ 40 ] for 156 countries, Kim and Kim [ 41 ] for 178 countries, Hashem [ 42 ] for developing countries. The ICT also reduces different types of mortality rates as found by Nyamawe and Seif [ 43 ] for Tanzania.…”
Section: Literature Reviewsupporting
confidence: 86%
“…Information and communication technology (ICT) also offers innumerable modern benefits for expanding life expectancy as identified by contemporary researchers (see Majeed and Khan [ 15 ], Lee and Kim [ 16 ], Aksentijevic [ 17 ]. Using two stage least squares and system GMM in cross-sectional and panel data from 1990–2014, Majeed and Khan [ 15 ] observed that ICT positively and significantly increased life expectancy and decreased infant mortality rates in 184 countries.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…This means that governments need to consider the long-term implications of the crisis while leveraging digitization and promoting structural transformation to build a stronger, more sustainable and resilient tourism economy [41]. Thus, optimal efforts and new breakthroughs are needed for economic recovery and business stability through innovation and the use of technology towards increasing business competitiveness in the global-market era [42]. Furthermore, product promotion and marketing through the use of information technology and support of good governance will accelerate the recovery of tourism and SME business activities.…”
Section: Travel-business Stagnation and Sme Business Turbulencementioning
confidence: 99%
“…Whether used for personal use or at home, for making purchases or payments, in education, transportation, in dealing with healthcare or public authorities, or by companies, banks, or other governmental institutions, these web-based devices (Nistor and Zadobrischi 2022;James and Abiola 2021;Lavric et al 2022;Avătămănit , ei et al 2021;Misra et al 2016) could be seen as essential for most people in society. Evidently, the high pace of research and technological advancement has contributed to permanent appearance of new tools and electronic equipment-related to ICT (Information and communications technology), in addition to the upgrading of the already existent devices) (Nguyen and Doytch 2021;Miron et al 2008;Tamaş and Năstase 2008;Isaila 2012;Vîrgolici 2014;Spiezia 2012;Karaman Aksentijević et al 2021;Farhadi et al 2012)-so that the process of extension of such facilities to new human activities (Tofan and Bostan 2022;Alhmiedat and Aborokbah 2021;Yeh 2010Yeh , 2015, some of them being unconceivable until recently, has been in full development.…”
Section: Introductionmentioning
confidence: 99%